2019
DOI: 10.18844/gjpr.v9i1.3928
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between cognitive ability and field of study

Abstract: The present study was conducted to investigate the existence of any possible relationship between the cognitive reflection test (CRT), numeracy and academic majors. The statistical population of this study consisted of 117 freshmen studying under the faculties selected from the University of Tabriz. The generalised structural equation modelling technique was employed for data analysis. The research results indicated that CRT and numeracy had positive and significant effects on high school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The findings from this study supported the results from previous research on the effect of cognitive ability on learning outcomes in physics learning and basic electronics [6][7][8][9][10], mathematical competencies [15], and STEM learning [26]. Cognitive ability also has been shown to have a positive effect on complex thinking skills and even has a significant and positive contribution to achievement in various fields [13]. Referring to the results from this study, cognitive ability was an important factor as one of the variables that affected students' achievement not only in physics but also in STEM.…”
Section: Fig 3 Mean Scores Of Pretest and Posttestsupporting
confidence: 88%
See 3 more Smart Citations
“…The findings from this study supported the results from previous research on the effect of cognitive ability on learning outcomes in physics learning and basic electronics [6][7][8][9][10], mathematical competencies [15], and STEM learning [26]. Cognitive ability also has been shown to have a positive effect on complex thinking skills and even has a significant and positive contribution to achievement in various fields [13]. Referring to the results from this study, cognitive ability was an important factor as one of the variables that affected students' achievement not only in physics but also in STEM.…”
Section: Fig 3 Mean Scores Of Pretest and Posttestsupporting
confidence: 88%
“…In addition to learning media, cognitive ability also determines student learning outcomes. Deldoost et al [13] and Sinha et al [14] revealed the effect of cognitive ability on student learning outcomes, particularly in the TVE fields of study. Andrew [15] discovered that cognitive abilities significantly affected student success in mathematical competencies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been emphasised in many studies that multilingualism positively affects linguistic development, as well as mental development (Tenekeci & Uzunboylu, 2020). According to these studies, multilingual children are more sensitive to language meanings and are more susceptible to linguistic processes when compared to monolingual children (Deldoost, Mohammadzadeh, Akbari & Saeedi, 2019). Recent studies have revealed that the ability of multilingual children to understand the linguistic structure is more advanced than monolingual children.…”
Section: Introductionmentioning
confidence: 99%